Windows of technological opportunity: do technological booms influence the relationship between firm size and innovativeness? - Harald Degner (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2010)
Many papers have been written about the effect of firm size on innovativeness, revealing a positive, a negative or a mixed impact. To this day, the so-called Schumpeterian hypothesis of the above-average innovativeness of large firms has been neither confirmed nor rejected, often because of insufficient data or a too-short observation period. Many studies concentrate only on a specific region or a specific sector, or they analyze a very short time period. Windows of technological opportunities, providing technological booms for both firms and sectors, have not yet been investigated. An analysis of Germany's chemical, metal and electronic-engineering sectors between 1877 and 1932 reveals that the sector-specific long-term relationship between firm size and innovativeness is negative, except during times of specific technological booms. In combination with firm-specific characteristics, this new aspect can contribute to a better understanding of the long-term relationship between firm size and innovativeness.
urn:nbn:de:bsz:100-opus-4399
Keywords: 330; Effect of firm size on innovativeness; technological boom; Schumpeterian hypothesis; Betriebsgröße; Innovation; Technischer Fortschritt; Technologiewahl; Konjunktur; Industriegeschichte; Deutschland (bis 1945)